2003
DOI: 10.1897/1551-5028(2003)022<1269:eocwho>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Culture Water Hardness on the Sensitivity of Ceriodaphnia Dubia to Copper Toxicity

Abstract: We examined whether the sensitivity of Ceriodaphnia dubia to copper toxicity was influenced by the hardness of the water in which they were reared or in which they were exposed. Organisms cultured in very hard water were 1.5-fold less sensitive to copper than those in moderately hard water. However, the hardness of the exposure water had a greater (2.5-fold) effect on copper median effective concentration (EC50s).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…In 24-h copper toxicity tests with larvae (glochidia) of wavy-rayed lampmussels (Lampsilis fasciola) tested in ASTM-reconstituted soft and moderately hard waters, an increase in copper EC50s (18-50 mg Cu/L) was observed [33]. Although some studies with fish and crustaceans have shown that increasing water hardness is correlated with increasing acute EC50s for copper [13,16,36], other studies with crustaceans have reported little or no amelioration of copper toxicity with increasing water hardness in acute toxicity tests [18,37] or in chronic toxicity tests [38,39]. Similarly, Pynnonen [35] reported that increasing water hardness from 4.5 to 58 mg Ca/L did not affect 24-h toxicity of copper to glochidia of swan mussel (Anodonta cygnea).…”
Section: Toxicity Testingmentioning
confidence: 99%
“…In 24-h copper toxicity tests with larvae (glochidia) of wavy-rayed lampmussels (Lampsilis fasciola) tested in ASTM-reconstituted soft and moderately hard waters, an increase in copper EC50s (18-50 mg Cu/L) was observed [33]. Although some studies with fish and crustaceans have shown that increasing water hardness is correlated with increasing acute EC50s for copper [13,16,36], other studies with crustaceans have reported little or no amelioration of copper toxicity with increasing water hardness in acute toxicity tests [18,37] or in chronic toxicity tests [38,39]. Similarly, Pynnonen [35] reported that increasing water hardness from 4.5 to 58 mg Ca/L did not affect 24-h toxicity of copper to glochidia of swan mussel (Anodonta cygnea).…”
Section: Toxicity Testingmentioning
confidence: 99%
“…It is important to separate the effects of water hardness and alkalinity, because each variable has a different mechanism of reducing metal toxicity. Although the effect of calcium and magnesium is accepted as competitively inhibiting metal uptake and, hence, toxicity [14][15][16], alkalinity directly affects metal speciation in solution through complexation with carbonate, which will impact on metal bioavailability [17,18]. These mechanisms need to be uncoupled if their effects are to be incorporated in models that can be applied to metal regulation such as the BLM [4], which uses physicochemical variables to predict the acute toxicity of metals, such as copper, to freshwater biota on a site-specific basis.…”
Section: Introductionmentioning
confidence: 99%
“…The metal concentrations required to show acute toxic effects to fish typically are 10 to 100 times higher than water quality guideline values. Recent studies have re-evaluated the influence of water hardness on the toxicity of copper to the cladoceran Ceriodaphnia dubia, showing that, to a large extent, copper toxicity does not alter with increasing water hardness (i.e., calcium and magnesium) in synthetic waters [16,18].…”
Section: Introductionmentioning
confidence: 99%
“…In the acclimation studies, we expected the acclimated P. promelas to have higher LC50 values (less susceptible to silver) than nonacclimated organisms, as has been previously demonstrated for copper and C. dubia [28]. However, no differences in silver toxicity were detected between P. promelas, which were acclimated to the test waters, and those held in laboratory water before testing ( Table 3).…”
Section: Resultsmentioning
confidence: 83%